Mucosal Sporotrichosis from Zoonotic Transmission: Descriptions of Four Case Reports - Yong Yaw Yeow; Xue Ting Tan; Lee Lee Low (MDPI AG, 2023)
Background: Sporotrichosis is a subacute or chronic mycosis caused by a dimorphic fungus of the genus Sporothrix. Zoonotic-transmitted sporotrichosis has become a major public health concern and is characterised by a different clinical pattern from the traditional epidemiology of sporotrichosis. Case presentation: We present the details of four patients with mucosal sporotrichosis with regional lymphadenopathy (three cases of granulomatous conjunctivitis and one case of nasal sporotrichosis). The patients' age range was between 23 to 46 years old and their gender was three female and one male patient. All four patients shared the same ethnicity, Malay, and they had a common history of owning domestic cats as pets. Sporothrix schenckii were isolated from all the culture samples and its antifungal susceptibility patterns were compared in the mycelial and yeast phases. All four patients recovered with oral itraconazole treatment, but the treatment duration was variable among patients. Conclusions: People who have a history of contact with domestic cats should be aware of the possibility of sporotrichosis infection. It can present in cutaneous, lymphocutaneous, disseminated, or systemic forms. Early treatment and the prevention of disease progression are more beneficial to patients. The published data concludes that antifungal treatment is highly efficacious, although the reported treatment duration is variable.